Metodología de cálculo tarifario para el acueducto de la Municipalidad de Paraíso - Cordero-Araya, Francisco Javier (Instituto Tecnológico de Costa Rica, 2016)
The rate of water services should ensure financial sustainability of the aqueduct, considering the possibilities of paying users without limiting access to water. In Costa Rica, although ARESEP defined a calculation methodology, this does not apply to all providers. In addition, the form of payment does not guarantee equal treatment between users of the same category as the amount per cubic meter is not the same for everyone recently, is trying to incorporate an efficiency factor, however, it depends on the development of goals for reduction of UFW. Clearly, not all providers have the financial or technical capacity to quantify this type of requirements. In the case of municipalities, these are not regulated remaining at liberty to estimate the rate. Therefore, this study looked at the design of a methodology of tariff calculation for the Aqueduct of the Municipality of Paradise existing tariff structures were analyzed and a methodology, which was validated through expert consultation was proposed. In addition, a survey of willingness to pay regarding the environmental cost was applied. He defined a base fee includes administrative costs and a fee according to consumption including operating costs, and maintenance, investment and debt service as well as an environmental cost. Within the cost of operating and maintaining an efficiency factor regarding infrastructure leakage index (ILI) it was included. a subsidy for low-income users are also incorporated. It was found that administrative costs represent 28.3%, the operating and maintenance 57.1%, the investment and debt service 12.2% and 2.4% environmental cost. The amount of the fee represents an increase of 24.0% compared to the present, this mainly because the current rate is three years upgrade, coupled with existing objects of expenditure that have not been covered
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2016.
Keywords: Sostenibilidad; ARESEP; Agua; consumo; Uso del agua; Estabilidad financiera